2022
DOI: 10.1101/2022.04.10.487801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A chemomechanical model of sperm locomotion reveals two modes of swimming

Abstract: The propulsion of mammalian spermatozoa during reproduction relies on the spontaneous periodic oscillation of their flagella. These oscillations are driven internally by the coordinated action of ATP-powered dynein motors that exert active sliding forces between microtubule doublets, resulting in bending waves that propagate along the flagellum and enable locomotion of the cell through the viscous medium. In this work, we present a chemomechanical model of a freely swimming spermatozoon that uses a sliding-con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
5
2
0
Order By: Relevance
“…This work extends their findings to the emergence of three-dimensional asymmetrical beating without internal asymmetries. Our results also confirm findings there and elsewhere 18 that nonlinear effects become important at parameters that induce high flagellar curvatures. Rode et al .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This work extends their findings to the emergence of three-dimensional asymmetrical beating without internal asymmetries. Our results also confirm findings there and elsewhere 18 that nonlinear effects become important at parameters that induce high flagellar curvatures. Rode et al .…”
Section: Discussionsupporting
confidence: 92%
“…This work extends their findings to the emergence of threedimensional asymmetrical beating without internal asymmetries. Our results also confirm findings there and elsewhere 18 that nonlinear effects become important at parameters that induce high flagellar curvatures. Rode et al 22 and Ling et al 47 showed that mechanical instabilities can lead to transitions between planar and three-dimensional beating for different types of internal driving patterns.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…5b does not change appreciably with the inclusion of non-local hydrodynamics through slender-body theory, as was reported recently in Ref. [58]. The wavelength of beating patterns in the decoupling region is approximately equal to the length of the flagellum L and this is observed in Chlamydomonas (see Fig.…”
Section: Discussionsupporting
confidence: 81%